2021
DOI: 10.3390/ijms22179307
|View full text |Cite
|
Sign up to set email alerts
|

p53 Activation in Genetic Disorders: Different Routes to the Same Destination

Abstract: The tumor suppressor p53 is critical for preventing neoplastic transformation and tumor progression. Inappropriate activation of p53, however, has been observed in a number of human inherited disorders that most often affect development of the brain, craniofacial region, limb skeleton, and hematopoietic system. Genes related to these developmental disorders are essentially involved in transcriptional regulation/chromatin remodeling, rRNA metabolism, DNA damage-repair pathways, telomere maintenance, and centros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…Abnormal p53 activation has been observed in several congenital syndromes, such as Diamond-Blackfan anemia and Fanconi anemia, that are caused by mutations in ribosome biogenesis or DNA repair pathways. Mouse models of these disorders in general can recapitulate human traits, and disorder-related phenotypes can be alleviated by inactivation of p53 ( Bowen and Attardi, 2019 ; Tsai et al., 2021 ). Therefore, our present result indicated that TAR syndrome belongs to a p53-activation-associated genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal p53 activation has been observed in several congenital syndromes, such as Diamond-Blackfan anemia and Fanconi anemia, that are caused by mutations in ribosome biogenesis or DNA repair pathways. Mouse models of these disorders in general can recapitulate human traits, and disorder-related phenotypes can be alleviated by inactivation of p53 ( Bowen and Attardi, 2019 ; Tsai et al., 2021 ). Therefore, our present result indicated that TAR syndrome belongs to a p53-activation-associated genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Such CaM inhibitors might find broad medical applications, as illustrated by Taylor and colleagues [ 68 ], who provided evidence that CaM inhibitors could be efficacious in rescuing a genetic disease (Diamond-Blackfan anemia, DBA) that results from increased expression of tumor suppressor protein 53. This study suggests that CaM inhibition may offer a potential therapeutic path for treatment of DBA and other diseases characterized by aberrant p53 activity [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 Although antagonists of p53 transcriptional activity provide prospective therapeutic applications, p53 inhibitors have not been applied in clinic. 29 Thus, discovering small-molecule inhibitors of p53 is an important research goal for generating drug leads of therapeutic strategies targeting p53 function. Our research provides a new choice for exploring the clinical significance of inhibiting p53 function.…”
Section: Discussionmentioning
confidence: 99%
“…NSC194598 protects mice from radiation toxicity via inhibiting transcriptional output . Although antagonists of p53 transcriptional activity provide prospective therapeutic applications, p53 inhibitors have not been applied in clinic . Thus, discovering small-molecule inhibitors of p53 is an important research goal for generating drug leads of therapeutic strategies targeting p53 function.…”
Section: Discussionmentioning
confidence: 99%